Principles Of Treatment Of Patients With Chronic Kidney Disease And Arterial Hypertension - N.M Abdurakhmanova; O.M. Norbo‘toyev (Global Scientific Publishing, 2024)
Chronic kidney disease (CKD) is a progressive kidney injury, more common in the elderly, women, patients with diabetes mellitus (DM) and/or arterial hypertension (AH). Currently, CKD is recognized as one of the leading causes of death worldwide. Another medical and social problem is hypertension, which is the most important cardiovascular risk factor worldwide and one of the main causes of CKD. The high prevalence and comorbidity of CKD and hypertension, as well as an unfavorable prognosis, determine the need for effective prevention and treatment of these conditions. The use of nephroprotective approaches in the treatment of CKD can significantly improve the prognosis both in patients with risk factors for the development of renal dysfunction and in patients with existing kidney disease. According to modern recommendations for the treatment of hypertension, patients with high-risk hypertension, including from the standpoint of nephroprotection, are shown combination therapy with drugs from two groups, preferably in one tablet. The article presents data confirming the efficacy of a fixed combination of an angiotensin-converting enzyme inhibitor and a dihydropyridine calcium channel blocker.
Keywords: chronic kidney disease; arterial hypertension; antihypertensive drugs